Metal‐organic framework‐based biomaterials for biomedical applications. Issue 3 (8th June 2021) - Luo, Gang; Jiang, Yanan; Xie, Chaoming; Lu, Xiong
Abstract: Metal‐organic frameworks (MOFs) refer to porous coordination materials that are formed from the assembly of metal ions and organic ligands. They have unique features, such as a large specific surface area, multiple active sites, easy functionalisation, and adjustable biocompatibility. MOFs have recently been widely used in the field of biomedical engineering owing to their unique structures and properties. This has enabled them to replace traditional materials and effectively address several problems. Through continuous development, MOF‐based biomaterials have been remarkably improved by clarifying the relationship between MOF structures and properties. As a result, they are being extensively studied in the fields of chemical and material science. MOF‐based biomaterials can meet the growing demands for efficient materials in biomedical applications. This review first discusses the basic structure of MOFs, followed by their preparation and functionalisation methods. The biomedical applications of MOF‐based biomaterials in the fields of antibacterial activity, tumour therapy, skin repair, and bone repair are then summarised. Finally, challenges and future perspectives in the biomedical applications of MOF‐based biomaterials are outlined.